Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Biomass-inherent nitrogen doping in utilized chopsticks carbon for alkaline electrolysis - PratimaDevi Sivasubramanian; Yen-Ping Peng; Po-Hsun Lin; Subramanian Sakthinathan; Te-Wei Chiu; Ching-Lung Chen (Biomass and Bioenergy, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Insertion of the PgRE1 retrotransposon into the promoter region of PgACS1, a system-2 ACC synthase gene, leads to variation in ripening ethylene production and the storability of different guava varieties - Margo Sulistio; You-Siang Liao; Hsin-Hung Yeh; Ching-Ping Lin; Hung-Yeh Hsieh; Chun-Ta Wu (Postharvest Biology and Technology, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Spatial variability of groundwater flow fields caused by nonstationary random input parameter processes - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Journal of Hydrology, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Analysis of chemosensitivity of tumor spheroids exposed to two-dimensional gradient of combination drugs in a hydrogel-based diffusion microfluidic platform - Kin Fong Lei; Yu-Ting Lin; Sai Kiran Reddy Boreddy; Ping-Ching Pai (Analytica Chimica Acta, 2024)

Study on the performance of highly doped copper tailings sand for concrete pavements using specific grading techniques - Sung-Ching Chen; Meng-Yao Gao; Wei-Ting Lin; Le-Ping Liu; Kinga Korniejenko (Minerals Engineering, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Stochastic Quantification of Spatial Variability of Flow Fields in Heterogeneous, Non-uniform, Confined Aquifers - Chuen-Fa Ni; Ching-Min Chang; Chi-Ping Lin; I-Hsian Lee (Transport in Porous Media, 2024)

Variability in the displacement of solute particles in heterogeneous confined aquifers - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Advances in Water Resources, 2024)

Decision tree analysis of thermal comfort in the courtyard of a senior residence in hot and humid climate - Ching-Yin Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Variability of travel time of solute particles in single fractures with spatially variable aperture - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Engineering Geology, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Biomechanical Evaluation of a Fin-type Implant Compared to Traditional Buttress Plate for the Stabilization of the Posteromedial Fragment in Tibial Plateau Split Fractures - Jian-Chih Chen; Kang-Ping Lin; Tien-Ching Lee; Yin-Chih Fu; Kun-Jhih Lin (Journal of Medical and Biological Engineering, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Injury feigning in the Savanna Nightjar: a test of the vulnerability and brood value hypotheses - Shu-Ping Tseng; Yung-Yi Lin; Yi-Ching Yang; Ying Wang; Wen-Loung Lin (Journal of Ornithology, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Inhibition of Peripheral TNF-α and Downregulation of Microglial Activation by Alpha-Lipoic Acid and Etanercept Protect Rat Brain Against Ischemic Stroke - Ming-Hsiu Wu; Chao-Ching Huang; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Obesity Exacerbates Rat Cerebral Ischemic Injury through Enhancing Ischemic Adiponectin-Containing Neuronal Apoptosis - Ming-Hsiu Wu; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Chao-Ching Huang; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Developing a reliable model for aquifer vulnerability - Cheng-Shin Jang; Chien-Wen Lin; Ching-Ping Liang; Jui-Sheng Chen (Stochastic Environmental Research and Risk Assessment, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

High Growth Rate Downregulates fumA mRNA Transcription but Is Dramatically Compensated by Its mRNA Stability in Escherichia coli - Hsiao-Hsien Lin; Ching-Hsueh Lin; Shiaw-Min Hwang; Ching-Ping Tseng (Current Microbiology, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

Sea level fluctuations on the east coast of Taiwan that overlie continental shelf break - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu; Yee-Ping Jia; Chih-Ming Ma (Stochastic Environmental Research and Risk Assessment, 2010)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Interleukin-1 receptor antagonist restores homeostatic function and limits multiorgan damage in heatstroke - Kun-Hung Shen; Chen-Kuei Chang; Mao-Tsun Lin; Ching-Ping Chang (European Journal of Applied Physiology, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Pulmonary actinomycosis: a case undergoing resection through video-assisted thoracic surgery (VATS) - Ming-shian Lin; Wea-lung Lin; Shi-ping Luh; Thomas Chang-yao Tsao; Tzu-ching Wu (Journal of Zhejiang University-SCIENCE B, 2007)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)